2019
DOI: 10.1038/s41419-019-1794-8
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS Sol narae cleaves extracellular Wingless to generate a novel active form that regulates cell proliferation in Drosophila

Abstract: s Wnt/ Wingless (Wg) is essential for embryonic development and adult homeostasis in all metazoans, but the mechanisms by which secreted Wnt/Wg is processed remain largely unknown. A Drosophila Sol narae (Sona) is a member of A D isintegrin A nd M etalloprotease with T hrombo S pondin motif (ADAMTS) family, and positively regulates Wg signaling by pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 77 publications
1
17
0
Order By: Relevance
“…Further analysis of sona suppressors revealed that sona itself and most suppressors are linked to Wg signaling 12,13 , which raised an interesting possibility that Pdm3 is also involved in Wg signaling. We noticed that pdm3 mutant larvae are slow in locomotion (Movie 1), implying a potential role of pdm3 in NMJ.…”
Section: Boutons Of Pdm3mentioning
confidence: 99%
See 2 more Smart Citations
“…Further analysis of sona suppressors revealed that sona itself and most suppressors are linked to Wg signaling 12,13 , which raised an interesting possibility that Pdm3 is also involved in Wg signaling. We noticed that pdm3 mutant larvae are slow in locomotion (Movie 1), implying a potential role of pdm3 in NMJ.…”
Section: Boutons Of Pdm3mentioning
confidence: 99%
“…We identified a new pdm3 allele, pdm3 m7 , as a suppressor of lethality induced by Sol narae (Sona) overexpression in a genetic screen. Sona is a fly ADAMTS (A disintegrin and metalloprotease with thrombospondin motif) whose family members are secreted metalloproteases important for cell proliferation, cell survival and development [12][13][14] . We have shown that Sona positively regulates Wingless (Wg) signaling and is essential for fly development, cell survival, and Wg processing [12][13][14] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to HSPGs, Wg receptor Dfz2 also predominantly localizes to the basal epithelium surface, from where it is endocytosed for signal initiation (Hemalatha et al, 2016). Interestingly, the Drosophila metalloproteinase Sol Narae (Sona) localizes to the basal extracellular matrix of the wing epithelium, where it cleaves extracellular Wg (Kim et al, 2016;Won et al, 2019). The resulting Wg-C-terminal fragment induces a discrete subset of Wg response genes to regulate cell proliferation specifically (Won et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…By probing the biological mechanisms of colon cancer, a number of related genes, including oncogenes and tumor suppressor genes have been identified (Xu G et al, 2017). A metalloproteinase of7 the disintegrin and metalloproteinases and the ThromboSpondin Motifs (ADAMTS) family contains 19 members, all of which retain a broadly similar modular structure (Kelwick et al, 2015;Won et al, 2019). According to the study of (Wang et al, 2011), ADAMTS12 expression exerted important impacts on suppressing colorectal cancer development.…”
Section: Introductionmentioning
confidence: 99%